Competitiveness Analysis to Increase Dusun Wangun Potential as a Tourism Village - Dian Kurnianingrum; Mulyani .; Chyntia Ika Ratnapuri (Jurnal Manajemen Indonesia, 2020)
In recent years, arise many tourism villages in Indonesia. Government through the Ministry of Village, Development of Underdeveloped Regions, and Transmigration and the Ministry of Tourism, continue to support the development of tourism villages in Indonesia. It proved that the tourism village programmed able to increase its resident welfare. Dusun Dusun Wangun in Gunung Puntang Bandung West Java is well known as a coffee-producing village. Puntang Coffee produced by Dusun Wangun is quite famous, it even won the first place in SCAA Atlanta United States. In fact, the village is also designed as a tourism village. However, its role as a tourism village rarely been heard. Whereas, that village has a lot tourism potential that can be highlighted and developed. Based on the description above, the researcher wants to find out what problems might hamper the development of Dusun Wangun as a tourism village. Researchers also want to gather information to understand the advantages and disadvantages possessed by Dusun Wangun as a tourism village. To assist the analysis, researchers used Porter Five Forces Analysis to answer research questions. The research data were obtained from interviews with residents and tourists who had visited Dusun Wangun. Data is collected to find out the strengths, weaknesses, suggestions, and other opinions to improve the competitiveness of Dusun Wangun. Hopefully, in the future, the results of this research can be used to determine the most appropriate strategy or solution to develop tourism in Dusun Wangun. Keywords—Competitiveness Analysis; Tourism Village; West Java Tourism; Economic Development; Porter Five Forces